2004
DOI: 10.1159/000077958
|View full text |Cite
|
Sign up to set email alerts
|

The Results of Cytogenetic Analysis with Regard to Intracytoplasmic Sperm Injection in Males, Females and Fetuses

Abstract: Objectives: To determine the incidence of chromosome abnormalities among couples for whom intracytoplasmic sperm injection (ICSI) treatment was indicated and fetuses conceived through the ICSI procedure. Methods: All cytogenetic results were evaluated retrospectively. Patients undergoing ICSI (n = 508) were classified according to the referring indications as: (1) males with severe infertility (87 azoospermia and 34 oligoasthenoteratozoospermia, OAT), (2) prior to ICSI (56 males and 61 females), and (3) follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
(34 reference statements)
0
3
1
Order By: Relevance
“…In the presented study, chromosomal abnormalities were detected in 5.4% of 92 azoospermic cases and no patients of 23 oligozoospermic cases. The chromosomal abnormality ratio in azoospermia was given as 12.5-31% [4,6,[23][24][25][26]. Although our results reflect a regional pattern of those referrals, comparison of our results with the review of the literature shows a relatively smaller incidence of chromosomal anomalies in azoospermia in our center.…”
Section: Discussioncontrasting
confidence: 56%
“…In the presented study, chromosomal abnormalities were detected in 5.4% of 92 azoospermic cases and no patients of 23 oligozoospermic cases. The chromosomal abnormality ratio in azoospermia was given as 12.5-31% [4,6,[23][24][25][26]. Although our results reflect a regional pattern of those referrals, comparison of our results with the review of the literature shows a relatively smaller incidence of chromosomal anomalies in azoospermia in our center.…”
Section: Discussioncontrasting
confidence: 56%
“…In the review by Mau-Holzmann (2005), only four comparable complex rearrangements have been reported: t(1;9;21), t(4;11;18), t(4;13;9) and t(8;13;16). In addition, Basaran et al (2004) detected a male with t(5;6;14) and Marchina et al (2007) a case with t(1;2;8). As stated by Chantot-Bastaraud et al (2008), the probability of finding chromosomally balanced spermatozoa for ICSI is very low in these cases.…”
Section: Chromosome Anomalies In Icsi Patientsmentioning
confidence: 99%
“…No studies have shown a gender predominance, especially as autosomal anomalies were more frequent [25,26]. However, it is very likely that inherited abnormalities are most often transmitted from the father, which predicts a higher prevalence in boys [27,28].…”
Section: Discussionmentioning
confidence: 99%